The Effect of Mung Bean (Phaseolus radiatus L.) Beverage with Red Ginger (Zingiber officinale var. rubrum) Addition on Total Cholesterol Levels in Female Hypercholesterolemia Patients at Gunung Sari Ilir Public Health Center - Riana Angelina; Rif’atul Amini; Resti Kusumarini Samben (Media Publikasi Cendekia Indonesia, 2025)
This study aims to analyze the effect of administering a mung bean beverage supplemented with red ginger on total cholesterol levels in female patients with hypercholesterolemia. The study utilized a quasi-experimental design with a non-equivalent control group approach. A total of 30 respondents were divided into two groups: treatment and control. The treatment group received the mung bean beverage with red ginger (250 ml) every morning for 14 days, while the control group received no intervention. Total cholesterol levels were examined using the Point of Care Testing (POCT) method before and after the intervention. Statistical analysis was performed using the paired t-test and the independent t-test. The results showed a significant decrease in total cholesterol levels in the treatment group from 240.33 ± 24.84 mg/dL to 207.07 ± 31.24 mg/dL (p = 0.000), with a mean difference of 33.27 mg/dL. Conversely, the control group experienced an increase in total cholesterol levels from 246.47 ± 28.65 mg/dL to 256.53 ± 27.51 mg/dL (p = 0.083). The independent t-test showed a significant difference between the two groups post-intervention (p = 0.000). The consumption of mung bean beverage with the addition of red ginger is effective in lowering total cholesterol levels in female patients with hypercholesterolemia. This intervention has the potential to be developed as a local food-based nutritional strategy for controlling dyslipidemia in primary health care